When should we think about Fabry disease? - Natalia Chojnacka; Radosław Cymer; Karolina Jurasz; Dominika Podgórska; Ewa Rzeska; Miłosz Sanecki; Karolina Tomczyk; Jakub Klarycki (Kazimierz Wielki University, 2024)
According to the European Union definition, a rare disease is a disease that occurs with a frequency of less than 5 per 10,000. Rare diseases pose a major diagnostic problem for physicians. Due to the often uncharacteristic symptoms and rarity of the disease, it can take a long time before a correct diagnosis and treatment is made. Fabry disease is classified as a rare disease. It is an X-linked hereditary syndrome caused by alpha-galactosidase A deficiency. This leads to accumulation of glycosphingolipids in tissues and dysfunction of many organs. The clinical picture is variable and dependent on residual alpha-galactosidase A activity. The classic form of the disease occurs most often in males due to the presence of only one X chromosome. When alpha-galactosidase A activity is partially preserved, a non-classical form develops, which is more commonly seen in the female sex. The most common clinical manifestations reported by patients are angiokeratoma, anhidrosis, diarrhoea or left ventricular hypertrophy. To diagnose Fabry disease, alpha-galactosidase A activity can be measured in whole blood - dry blood drop test (DBS), plasma or leukocytes. Fabry disease can be treated effectively, but treatment must last for life. The treatments reimbursed in Poland are agalsidase alfa and beta preparations and migalastat.